Emerging Leadership in the Pauline Mission: A Social Identity Perspective on Local Leadership Development in Corinth and Ephesus - Barentsen, Jack (0, 2011)
Intro -- Title Page -- Foreword -- Preface -- Abbreviations -- Chapter 1: Introduction -- Chapter 2: The Ideological Challenge of Church Leadership Studies -- Chapter 3: The Social Identity Model of Leadership -- Chapter 4: Realigning Emerging Leadership with Christian Social Identity in 1 Corinthians -- Chapter 5: Reestablishing Paul's Leadership as Model in 2 Corinthians -- Chapter 6: Leadership Legitimation and Empowerment in Ephesians -- Chapter 7: Structuring Leadership and Group Participation in 1 Timothy -- Chapter 8: Correcting Leadership Misconceptions and Establishing Succession in 2 Timothy -- Chapter 9: Conclusions and Implications: Emerging Leadership in the Pauline Mission -- Bibliography.